Evaluation of Dutasteride-Loaded Liposomes and Transfersomes for Follicular-Targeting for Androgenic Alopecia Topical Treatment - Jayanaraian F. M. Andrade; Breno N. Matos; Rafael V. Rocho; Geisa N. Barbalho; Marcilio Cunha-Filho; Guilherme M. Gelfuso; Taís Gratieri (Pharmaceutics)
Background/Objectives: Although androgenic alopecia is the most prevalent among non-cicatricial alopecia, it still lacks an effective and safe treatment. Dutasteride (DUT) shows promising results in hair regrowth; however, oral DUT intake causes serious sexual adverse events. Hence, we produced liposomes with different bilayer structures and evaluated the capability of such systems in increasing DUT accumulation in the hair follicles. Methods: In vitro skin penetration tests were performed with porcine ear skin, and the follicular targeting factor (Tf) was calculated as the ratio between DUT amount in HFs and DUT recovered from the sum of all skin layers. Results: While the stiffer DUT-loaded liposome was not able to target the hair follicles in 12 h (Tf = 0.15), a DUT-loaded liposome with an edge activator in its composition, i.e., transfersomes, promoted better control over DUT release and a higher Tf (0.32) (p < 0.005). Conclusions: Transfersomes present higher affinity with DUT providing a better controlled release; hence, they are a better option for DUT follicle targeting compared to liposomes. Further formulation optimizations are needed aiming to prolong such targeting effect.